Constructing ideal body appearance for women: a multimodal analysis of a TV advertisement - Böhlke, Rossana de Felippe (2008)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão. Programa de Pós-Graduação em Letras/Inglês e Literatura Correspondente